Digit ratio (2D:4D) profile of varsity rugby players / Mohd. Zulkhairi Mohd. Azam …[et al.] - Mohd Azam, Mohd Zulkhairi; Sariman, Mohd Hanifa; Wan Norman, Wan Mohd Norsyam; Ronny Linoby, Adam Feizrel Linoby; Mohamad Zaki, Muhammad Sufyan; Mohamed Afandi, Mohamad Azizul (2013)
High performance in sport and aggression has been reported to correlate with low digit ratio (2D:4D) due to high amount of testosterone received in the womb. In this study rugby is chosen because Universiti Teknologi MARA (UiTM) Pahang's rugby team is regarded as one of the top 3 teams among the UiTM branches rugby team, and also among other varsity rugby teams in the nation. The players were very talented as most of them have vast experiences playing for their own respective states from youth to the senior team level. Furthermore, rugby has been associated with aggression which is a direct relation to the production of hormone testosterone. Thus, this study was conducted in order to investigate the digit ratio profile of the rugby players (n=22). Their mean age score was 19.3±0.95 years old and 2D:4D were measured by using the MicroDicom software Based on the descriptive analysis, the findings showed that 20 players out of 22 players had low 2D:4D, with only 2 players had high 2D:4D with overall mean score .95±.03I mm and the highest 2D:4D recorded were 1.02 mm. The results were in line with the other past related evidence which stated that low 2D:4D were highly correlated with sporting ability and high performance across variety of sports. Therefore, we concluded most of the players in the current rugby team posed low 2D:4D, and may correlate with the team high rugby performance that contributes to most of their recent success.